Design and realization of a 3-K cryostat for a 10-cm ultrastable silicon cavity - Wang, Wen-Wei; Chen, Zhi-Ang; Zhang, Han; Du, Shize; Wu, Rui; Qiao, Chang; Kuang, Shiyin; Zhang, Xibo (Frontiers in Physics, 2023)
Crystalline optical cavities operating at cryogenic temperatures provide a promising route for realizing the next generation of ultrastable lasers with extremely low thermal noise floor. However, it remains challenging to realize a closed-cycle cryostat for cooling a relatively long cavity to very low temperatures. Here we report on the design and experimental realization of a cryostat operating continuously at 3.1 K for an ultrastable 10-cm silicon cavity. Based on a combination of active temperature control and passive thermal damping, we realize at 3.1 K a two-second temperature instability of 6 × 10−8 K for the cavity. By implementing separate supporting structures for the cryocooler and the sample chamber, we realize vibration control on the 1 × 10−7g level at one second in each spatial direction, where g is the gravitational acceleration. With all these features, our cryostat can support an ultrastable silicon cavity with instability near its fundamental thermal noise floor at averaging time of 1–50 s. With proper upgrading, our platform holds promise for realizing ultrastable lasers with 3 × 10−17 or better frequency stability, which will in turn enable numerous studies on precision metrology and quantum many-body physics.